HUBUNGAN KARAKTERISTIK REMAJA DAN SOSIODEMOGRAFI KELUARGA DENGAN KEJADIAN OBESITAS PADA REMAJA DI SMA NEGERI 1 KUTA - Darma Yudha, I Gede Esa; Adhi, Kadek Tresna (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024, 2025)
Obesity is a nutritional problem that is experienced by many teenagers today. Badung Regency is the first district in Bali Province with the highest obesity rate, which is 41.52%. The purpose of this study was to look at the relationship between adolescent characteristics and family sociodemography with the incidence of obesity in adolescents at SMA Negeri 1 Kuta. This research is an analytic observational study with a cross-sectional design. The research sample consisted of 104 youth aged 15-18 years from SMAN 1 Kuta who were willing to become research respondents. This study found that the characteristics of adolescents, gender (p value = 0.013), sociodemographic family, father's education (p value = 0.014), mother's education (p value = 0.000) and father's occupation (p value = 0.033) were significantly related to the incidence of obesity. It is necessary to increase the knowledge of adolescents regarding food consumption that causes obesity, this can be done through collaboration between the Health Office, Community Health Centers and schools to carry out routine counseling about obesity. Keywords: Obesity, Adolescent Characteristics, Family Sociodemographics, Lifesty